Counteracting action of Bacillus stratosphericus and Staphylococcus succinus strains against deleterious salt effects on Zea mays L. - Oliva, Gianmaria; Vigliotta, Giovanni; Terzaghi, Mattia; Guarino, Francesco; Cicatelli, Angela; Montagnoli, Antonio; Castiglione, Stefano (Frontiers in Microbiology, 2023)
Salinization of the soils is a process of progressive accumulation of salts, as: sulphates, sodium, or chlorides into the soils. The increased level of salt has significant effects on glycophyte plants as rice, maize, and wheat, which are staple foods for the world’s population. Consequently, it is important to develop biotechnologies that improve crops and clean up the soil. Among remediation methods, there is an environmentally friendly approach to ameliorate the cultivation of glycophyte plants in saline soil: namely, the use of microorganism tolerant to salt with growth promoting features. Plant Growth Promoting Rhizobacteria (PGPR) can improve plant growth by colonizing their roots and playing a vital role in helping plants to establish and grow in nutrient-deficient conditions. The aim of our research was to test in in vivo halotolerant PGPR, isolated and characterized in in vitro in a previous work conducted in our laboratory, inoculating them on maize seedlings to improve their growth in the presence of sodium chloride. The bacterial inoculation was performed by seed coating method, and the produced effects were evaluated by: morphometric analysis, quantization of ion contents (sodium, potassium),produced biomass, both for epigeal (shoot) and hypogeal (root) organs, furthermore, by measuring of salt-induced oxidative damage. The results showed an increase in biomass and sodium tolerance, and even a reduction of oxidative stress in seedlings pretreated with a PGPR bacterial consortium (Staphylococcus succinus + Bacillus stratosphericus) over the control. Moreover, we observed that salt reduce growth and alters roots system traits of maize seedlings, whilst bacterial treatment improves plant growth and partially restore roots architecture system in saline stress conditions. Therefore, the PGPR seed coating or seedlings treatment could be an effective strategy to enhance sustainable agriculture in saline soils thanks to the protection of the plants from their inhibitory effect.